Effect of Cu additions on mechanical properties of Ni3Sn4-based intermetallic compounds: First-principles calculations and nano-indentation measurements. (June 2019) - Bi, Xiaoyang; Hu, Xiaowu; Jiang, Xiongxin; Li, Qinglin
Abstract: The (Ni, Cu)3 Sn4 phase as intermetallic compounds (IMCs) plays an important role in evaluating reliability of solder joints. The first-principles calculations were performed to investigate the phase stability, mechanical properties and electronic structures of Ni3 Sn4 and Ni2.5 Cu0.5 Sn4 IMCs. The results shows that the doping of Cu atom not only reduced the phase stability but also weakened the mechanical properties of Ni3 Sn4 crystal structure. Meanwhile, all studied Ni3 Sn4 -based structures were structural stability. Moreover, the anisotropy of Ni2.5 Cu0.5 Sn4 (2a site) was strongest while that of Ni2.5 Cu0.5 Sn4 (4i site) was the weakest. Based on analysis of electronic structures, it indicated that the ionic bonding of NiCu in Ni2.5 Cu0.5 Sn4 structure was weaker than covalent bonding of nearest-neighbor Ni in Ni3 Sn4, which led to an energy reduction with the formation of banding states. By means of nano-indentation measurements, the young's modulus and hardness were measured to be 135.3 ± 8.4 GPa and 5.0 ± 0.63 GPa for Ni3 Sn4 while 126.3 ± 7.6 GPa and 4.7 ± 0.72 GPa for (Ni, Cu)3 Sn4, respectively, which were close to the value of calculated results. Highlights: Mechanical properties of Ni3 Sn4 and Ni2.5 Cu0.5 Sn4 were investigated by first-principles calculations. Young's modulus and hardness of Ni3 Sn4 and (Ni, Cu)3 Sn4 were determined by nano-indentation. The doped Cu atom weakened the mechanical properties of Ni3 Sn4 crystal structure.